2020
DOI: 10.3389/fmats.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Insight Into Au-Doped MoS2 for Sensing C2H6 and C2H4

Abstract: First-Principles Insight Into Au-Doped MoS 2 for Sensing C 2 H 6 and C 2 H 4 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
(38 reference statements)
2
9
0
Order By: Relevance
“…Consequently, in the cases of NO on Al-doped WS 2 , NO on P-doped WS 2 , and SO 2 on Al-doped WS 2 , the bandgap width of material had an evident change after the gas molecules were adsorbed. Previous studies have shown that a narrowed bandgap means lower kinetic stability, higher chemical activity, and a more natural electron transition from the valence band to the conduction band [31,32]. Thus, after gas adsorption, evident bandgap changes of doped materials made them possible to be sensitive substrates to detect the existence of gas molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, in the cases of NO on Al-doped WS 2 , NO on P-doped WS 2 , and SO 2 on Al-doped WS 2 , the bandgap width of material had an evident change after the gas molecules were adsorbed. Previous studies have shown that a narrowed bandgap means lower kinetic stability, higher chemical activity, and a more natural electron transition from the valence band to the conduction band [31,32]. Thus, after gas adsorption, evident bandgap changes of doped materials made them possible to be sensitive substrates to detect the existence of gas molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Au doped monolayer MoS 2 has high charge transfer and strong orbital hybridization ability. Doping Au atoms affect the electronic structure of MoS 2 monolayer, thus improving the adsorption capacity, so that the adsorption structure of C 2 H 6 and C 2 H 4 molecules on Au doped MoS 2 monolayer is relatively stable (Qian et al, 2020). In conclusion, although there are some reports on the surface activity of doped monolayer MoS 2 , the adsorption of formaldehyde on the surface of transition metal Zn doped MoS 2 has not been confirmed.…”
Section: Introductionmentioning
confidence: 82%
“…In particular, the figure suggests that the decoration/doping of metal/hetroatom over the base materials will enhance the catalytic reaction for specific gases and form the charge accumulation depletion region to improve the sensing performances. Reproduced from multiple sources with permission from References [18,41,42,46,[80][81][82][83][84][85][86][87][88][89][90][91]. Copyright 2016 Elsevier [18], copyright 2019 Elsevier [41], copyright 2016 Elsevier [42], copyright 2020 ACS [46], copyright 2020 [80], copyright 2019 Elsevier [92], copyright 2006 ACS [82], copyright 2007 ACS [83], copyright 2013 Elsevier [84], copyright 2014 Elsevier [85], copyright 2016 Elsevier [86], copyright 2018 ACS [87], copyright 2015 Elsevier [88], copyright 2014 Elsevier [89], copyright 2013 Nature [90], and copyright 2012 ACS [91].…”
Section: Figurementioning
confidence: 99%
“…However, they proposed that the application of a perpendicular electric field promotes gas adsorption on the MoS 2 surface [99]. More recently, Qian et al [80] explored the effect of Au doping on 2D MoS 2 monolayer sheets for C 2 H 6 and C 2 H 4 molecule detection. After Au doping, enhancement in adsorption energies and charge transfer between detection molecules and MoS 2 monolayer was noted.…”
Section: Figurementioning
confidence: 99%